Stadium attendance demand during the COVID-19 crisis: early empirical evidence from Belarus. Issue 18 (24th October 2021) - Reade, J. James; Schreyer, Dominik; Singleton, Carl
ABSTRACT: In this note, we consider early evidence regarding behavioural responses to an emerging public health emergency. We explore patterns in stadium attendance demand by exploiting match-level data from the Belarusian Premier League (BPL), a football competition that kept playing unrestricted in front of spectators throughout the global COVID-19 pandemic, unlike all other European professional sports leagues. We observe that stadium attendance demand in Belarus declined significantly in the initial period of maximum uncertainty. Surprisingly, demand then slowly recovered, despite the ongoing inherent risk to individuals from going to a match.